SIRANG SO SIRANG (PISAH TIDAK PISAH) DALAM ETNIS BATAK TOBA KISTEN (STUDI KASUS PAANGAN SUAMI ISTRI DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR) - Manik, Friska; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Christian teaching and tradition forbids divorce, as in the Christian Scriptures is written inMatthew 19: 6 "So they are no longer two, but one. Therefore what God has joined together, letno one separate. " Likewise with the Batak Toba oppose divorce. Sirang so sirang is avoidedthroughout the Batak Toba. The impact it is very detrimental to both the families of both the menand women of the party. Wedding costs are pretty much spent, especially women sinamot costsshould be considered in order to avoid divorce. Mental development of children is also supposedto inhibit them to divorce. Batak Toba delivered through Hula-hula ie Bones says tung naso soHamu marsirang, so sinirang hamatean ni "(can not divorce except as separated by death ordeath). Customs and religion that forbids divorce no longer feared by Batak Toba society ashappened in the district of Bangko Pusako where there are 6 couples Batak Toba ethnicChristian experience Sirang so sirang (separation not separated). Factors causing them toexperience sirang so sirang (separation not separated) is social media, infidelity, not havingoffspring, shifting the role of parents and domestic violence. Some parents of the sixth couple toreconcile that their families back together and there are also parents who support their childrento get married again because the partner can not have offspring.Keywords : Sirang so sirang, Marriage, Batak Toba